PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN - Duroah Duroah; Tri Sayekti; Kristiana Maryani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
Cognitive development is a change that occurs in thinking, intelligence and children’s language to provide reasons so that children can remember, strategize creatively, think how to be able to solve problems and be able to connect sentences into meaningfull talks. This study aims to determine the effect of the cooperative learning model type make a match on the cognitive development of children aged 4-5 years. The study was conducted in group A at TKIT Raudhatul Jannah Cilegon- Banten. The method used in this study is quasi-experimental research with a village nonequivalent control group design with a sample of 42 children. The results showed that the average cognitive ability of the experimental class children at pretest was 46.09 while the posttest was 48.52, an increase of 2.43% and for the control class pretest was 48.23 while at posttest was 48.66 then an increase of 0.43% could be concluded that there was a significant effect of the use of the cooperative learning model make a match type on the cognitive development of children aged 4-5 years.